God in Modern Philosophy - Collins, James, 1917-1985 (Chicago, Henry Regnery Company, 1959)
Examines the main philosophical approaches that have been taken toward God since the beginning of the fifteenth century, showing throughout the often decisive role which the theme of God's existence, nature and relation to the world has played in the development of modern philosophy
New Approaches to God through Faith and Reason -- The Skeptical Assault upon Knowledge of God -- God as a Function in Rationalist Systems -- Empiricism and the Neutralizing of God -- The Enlightenment: Battleground Over God -- Kant on God -- God and the Hegelian Absolute -- The Emergence of Atheism -- God Finite and in Process -- The Heart's Way to God -- Toward a Realistic Philosophy of God
Includes bibliographical references and index
Keywords: God -- History of doctrines; Philosophy, Modern; God; Philosophy; Philosophy